Successful expressing of phraseological units - Mubashira Barotova (International Consortium of Education and Culture Research Studies, 2019)
This article deals with the lexical and morphological formation of phraseological units that is idioms. Besides, the difference between words word combinations and idioms are analyzed thoroughly in the English and Uzbek languages comparatively.